Relationship between skin colour, conjunctivitis, and dermatitis in captive Caiman latirostris in Argentina - Hilevski Loreto, Samuel (2023)
The commercial production of crocodilians for skin and meat has been considered an important industry in the world, with skin being the most valuable product, while the meat is considered a by-product. This study was designed to identify some diseases that can affect crocodilians farmed in Argentina, examining the relationships between skin colour and these diseases. Each caiman was classified according to their skin colour and kind of diseases (conjunctivitis or dermatitis). In broad-snouted caimans the prevalence of conjunctivitis was 0.41, and dermatitis was 0.23. Statistical tests indicate that there may be a relationship between the skin colour and health status of the caiman, where the dark–skin animals appear healthier (35.76%) than the light–skin animals (15.89%), where these last are more vulnerable to suffer ocular diseases, and skin diseases at the same time (14.57%). In addition, the body mass and length of healthy animals (dark and light) were higher than caimans with eye disease or with both associated diseases. These results may help crocodilians farms caring by isolation of susceptible animals, establishing stricter criteria for health status. This may imply a decrease in diseases that affect the quality of the skin and the loss of individuals, with a consequent increase in profits obtained by the industry.